CGRP-antibodies, topiramate and botulinum toxin type A in episodic and chronic migraine: A systematic review and meta-analysis. (October 2021) - Frank, Florian; Ulmer, Hanno; Sidoroff, Victoria; Broessner, Gregor
Background: The approval of monoclonal antibodies for prevention of migraine has revolutionized treatment for patients. Oral preventatives are still considered first line treatments as head-to-head trials comparing them with antibodies are lacking. Methods: The main purpose of this study was to provide a comparative overview of the efficacy of three commonly prescribed migraine preventative medication classes. For this systematic review and meta-analysis, we searched the databases CENTRAL, EMBASE, and MEDLINE until 20 March 2020. We included RCTs reporting the 50% response rates for topiramate, Botulinum Toxin Type A and monoclonal antibodies against CGRP(r). Studies were excluded if response rates were not reported, treatment allocation was unclear, or if study quality was insufficient. Primary outcome measure were the 50% response rates. The pooled odds ratios with 95% confidence intervals were calculated with the random effects model. The study was registered at PROSPERO (CRD42020222880). Findings: We identified 6552 reports. Thirty-two were eligible for our review. Studies assessing monoclonal antibodies included 13, 302 patients and yielded pooled odds ratios for the 50% response rate of 2.30 (CI: 2.11–2.50). Topiramate had an overall effect estimate of 2.70 (CI: 1.97–3.69) with 1989 included patients and Botulinum Toxin Type A achieved 1.28 (CI: 0.98–1. 67) with 2472 patients included. Interpretation: Topiramate, botulinum toxin type A and monoclonal antibodies showed higher odds ratios in achieving a 50% response rate compared to placebo. Topiramate numerically demonstrated the greatest effect size but also the highest drop-out rate.